Woman Resistance against NAZI Regime Reflected in the Book Thief Novel - Windratama, Farras; Prastiwi, Yeny (Universitas Muhammadiyah Surakarta, 2019)
The research aims to investigate woman resistance against Nazi Regime in The Book Thief novel written by Markus Zusak. In analyzing The Book Thief, this research using the liberal feminist theory and theory of resistance of James Scott which includes public resistance and hidden resistance. The research belong to qualitative research. The research is focused in analyzing the indicator of main character’s resistance towards Nazi. By analyzing main character’s background, social relation and discrimination, the result of the research shows that the indicator of main character resistance are classified into four forms which consist ideology differences, making alliance with Nazi enemy, humiliation which leads the main character to resistance, and feeling empathy towards other race and ethic. Thus, The Book Thief novel are written in order to give the reader awareness towards woman resistance during Nazi Regime.